Idiopathic pancreatitis with splenic artery pseudoaneurysmv in a child: a rare presentation - Tiwari, Charu; Sandlas, Gursev; Jayaswal, Shalika; Shah, Hemanshi (International Surgery Journal, 2016)
Splenic artery pseudoaneurysms are a rare complication of pancreatitis and abdominal trauma in children. We report a case of splenic artery pseudoaneurysm complicating pancreatitis (idiopathic) that was managed by transcatheter angioembolization.